Synthesis and Characterization of Novel Pyridine and Pyrimidine Based 1,2,4-Triazoles with Nematicidal Activity - Reddy, B. Satyanarayana; Reddy, B. Srinivasa; Rao, Chowdoji; Subha, M.C.S. (Asian Journal of Chemistry, 2015)
A series of new 2-phenyl-pyrido[2,3-e]-[1,2,4]triazolo[1,5-c]pyrimidine and its derivatives (5a-f) have been synthesized conveniently by cyclization of N-(4-imino-4H-pyrido[2,3-d]pyrimidin-3-yl)-benzamide and its derivatives (4a-f). The synthesis of title compounds commenced from commercially obtainable 2-amino-3-cyanopyridine (1) and by including N-(3-cyano-pyridin-2-yl)-formimidic acid ethyl ester (2) and benzoic acid N’-[(3-cyano-pyridin-2-ylimino)-methyl]hydrazide and its derivatives (3a-f) as intermediates. The chemical structures of all newly discovered compounds were established by IR, 1H NMR and 13C NMR, mass spectral data and elemental analysis. Further, the target compounds have been used to find their nematicidal activity towards two well known nematicides such as Ditylenchus myceliophagus and Caenorhabditis elegans.